School Community's Perceptions of Factors Influencing Students' Grade IX School Leaving Examination Results. - Najafova, Fidan (ADA University, 2023)
This study aims to reveal the factors affecting students’ results in the 9th grade school leaving exams. The study addressed the problem regarding the 9th grade students low performance in school leaving exams in Azerbaijan. For this reason, this study tried to contribute to the local literature by exploring the difficulties faced by 9th grade students in public schools in the process of preparing for the final exams and investigating the issues related to the problem. The main interested parties, principals, teachers, students, and parents, were involved in discussions, and their beliefs, perceptions, and suggestions regarding the problem were explored. In addition to two urban schools, research was also conducted in a rural school. 47 people, including 3 school principals, 15 students, 17 teachers, and 12 parents, were involved in the research process. To explore and understand participants’ perceptions individual face-to-face interviews were conducted with three principals. In addition, focus group discussions were held with teachers, students, and parents. Face-to-face focus group discussions were conducted with the participants of urban schools, whereas online focus group discussions were conducted with the participants of rural schools. Although, during the discussions, the participants voiced different opinions about the factors contributing to students' performance in the school leaving exams, four main themes emerged by the researcher: 1) student's personal qualities and attitude towards education, 2) school-related factors (including lack of technical equipment and class size) 3) teacher-student relationship 4) family's attitude towards their child's education. RunningR The results of this study may pave the way for further research on improving student achievement in 9th grade school leaving examinations in Azerbaijan and stimulate the initiatives and cooperation of relevant institutions on the problem.
Keywords: Academic achievement -- Azerbaijan; Educational tests and measurements -- Azerbaijan; Parent-teacher-student relationships -- Azerbaijan